LONG-TERM VARIABILITY OF THE ABSOLUTE ANNUAL MINIMUM WATER FLOW OF THE RIVERS OF UKRAINE - Obodovskiy, O.; Lukianets, O.; Pochievets О.; Moskalenko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Studies of the variability of the minimum flow of water, which relates to the extreme regime characteristics of river water flow during periods of low water, are relevant. Such information, in general, is the limiting criteria for water consumption, water use and protection of water resources from pollution and depletion, and sometimes are indicators of danger and catastrophe, in particular, during periods of prolonged droughts. This is especially important in the conditions of modern climate change, in which the probability of occurrence of extreme hydrological phenomena increases significantly. To assess the long-term variability of the absolute annual minima of the flow of water from the rivers of Ukraine, sequences of minimum daily average water flows for a multi-year period from 294 gauging stations from the beginning of the observations to 2015 inclusive were formed. The methods of statistical processing of random variables (for determining the norms of runoff, coefficients of variation and asymmetry) and random functions (for constructing integral difference curves) were used. The study of the spatial specifics of changes in the absolute minima of the water flow of the rivers of Ukraine is based on the "Hydrographic zoning of Ukraine’s territory". According to it, the territory of Ukraine is divided into hydrographic units — nine areas of river basins and nine sub-basins. The absolute annual minima of river runoff on the territory of Ukraine are recorded during periods of summer-autumn or winter low-water periods. High values of absolute annual minima in the modules of water flow are observed on the rivers of the Carpathian region and reach 8,7 l · s – 1 · km – 2. Basically, such values are on mountain rivers with small catchment areas; on rivers with large catchment areas that extend from the mountain and foothill areas of their flow to the plains, up to 0,9 l · s – 1 · km – 2; on the rivers of the Crimea, the absolute annual minimums in the water flow modules, in the vast majority, vary from 0,0 to 1,8 l · s – 1 · km – 2. Regarding flat river basins, for the rivers of the Vistula basin, the sub-basins of the Pripyat and the Desna, the left-bank part of the Dniester river basin, the range of changes in the absolute annual minima of the water flow modules is 0,20 ÷ 2,9 l · s – 1 · km – 2. To the south of the indicated flat river basins, the ranges of absolute annual minima are gradually decreasing. On the rivers of the sub-basin of the Middle Dnieper there is 0, 19 ÷ 1,19 l · s – 1 · km – 2, the subbasin of the Lower Dnieper – 0,04 ÷ 0,42 l · s – 1 · km – 2, the basin of the Southern Bug – 0,09 ÷ 1,75 l · s – 1 · km – 2. And in the basin of the rivers of the Black Sea region there is 0,0 ÷ 0,001 l · s – 1 · km – 2. For river basins of the flat part of Ukraine, the variation of annual minima is within 0,30 ÷ 2,83, the smaller one is the range of variability for the rivers of the Carpathian region – 0,20 ÷ 0,90. The asymmetry coefficients of the minimum river flow during the year for the whole territory of Ukraine range from negative -0,11 ÷ -2,01 to positive values 1,30 ÷ 6,4. The long-term variability of the absolute annual minima of the water flow of the rivers of Ukraine has been studied. Analysis of generalized difference integral curves for the entire set of rivers within the basins and sub-basins of the hydrographic zoning of Ukraine showed for the period of joint observations from 1947 to 2015 marked cyclic component. It manifests itself in a long period of decreasing absolute annual minimum values until 1968-1974, then there is an increase, and at the present time period, after 2006-2010, there is a tendency to decrease.